2020
DOI: 10.1680/jwama.18.00094
|View full text |Cite
|
Sign up to set email alerts
|

A physics-based routing model for modular green roof systems

Abstract: The ability of green roof systems to impact stormwater runoff from buildings has been covered in many research studies. However, a lot of these studies looked at long-term retention, with much less work focused on how to model a green roof's response to larger design storms. Work that has examined flow routing for individual rainfall events has focused on empirical routing models that are tuned to the specific roof being modelled. This paper presents a new physics-based model for flow routing based on the gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Theoretical routing models have been developed and applied to green roof systems to predict rainfall-runoff behavior [9], to calculate the system's initial abstraction [10], to quantify the detention performance [11], and to quantify their ability to reduce the peak discharge from major rainfall events [12]. However, in general it is seen that extensive green roof systems have limited storage capacity relative to large design storm events and, therefore, have minimal impact on peak discharge during these more significant rainfall events.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Theoretical routing models have been developed and applied to green roof systems to predict rainfall-runoff behavior [9], to calculate the system's initial abstraction [10], to quantify the detention performance [11], and to quantify their ability to reduce the peak discharge from major rainfall events [12]. However, in general it is seen that extensive green roof systems have limited storage capacity relative to large design storm events and, therefore, have minimal impact on peak discharge during these more significant rainfall events.…”
Section: Introductionmentioning
confidence: 99%
“…However, in general it is seen that extensive green roof systems have limited storage capacity relative to large design storm events and, therefore, have minimal impact on peak discharge during these more significant rainfall events. In an experimental and modeling study of modular extensive green roof systems specifically looking at major rainfall events, Martin et al [12] showed that the drawdown time for a typical modular green roof system is of the order of a few minutes. These results match what has been seen for non-modular green roofs as well [13].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations